Imidazole propionate in type 2 diabetes mellitus and cardiovascular diseases: a mini review - Xu, Qian; Wang, Wenting; Li, Yiwen; Liu, Yanfei; Liu, Yue (Frontiers in Immunology, 2024)
Oral and gut microbiota can interact with the host by producing a diverse range of bioactive metabolites, thereby influencing overall host health. Imidazole propionate (ImP), a histidine-derived metabolite produced by microbes associated with diabetes mellitus, has attracted considerable attention on account of its roles in metabolic and cardiovascular diseases. In this article, we review the metabolic pathways of ImP, as well as its roles and therapeutic potential in type 2 diabetes mellitus and cardiovascular diseases. Future research should focus on key enzymes and regulatory factors in the ImP metabolic pathway, interactions with other metabolites, and conduct large-scale clinical studies to gain a more comprehensive understanding of the role of ImP in diverse populations and disease contexts. Moreover, targeted interventions against ImP could provide novel strategies for preventing and treating metabolic and cardiovascular diseases.